A Probabilistic Model to Improve Reconciliation of Estimated and Actual Grade in Open Pit Mining - Parhizkar, A.; Ataei, M.; Moarefvand, P.; Rasouli, Vamegh (Springer, 2012)
Many of the open-pit mines suffer from the lack of reconciliation between estimated and actual grades. In a mining operation, grade reconciliation is the comparison between the values of the estimated grade calculated in exploration stage and the actual grade obtained from more reliable data such as blast holes’ samples. Many different factors affect the degree of reconciliation in a mining operation. In this paper, the factors related to estimated grade which affect the reconciliation process in the exploration stage of the orebody are investigated. These factors constitute the sources of uncertainty for the upcoming phases of the mining life. Among these parameters, the inherent variability, statistical uncertainty, and systematic uncertainty are the most important factors. In this work, these parameters are studied in further detail, and, accordingly, for each of these uncertainties, a correction factor is determined in the proposed model. The model was applied to the study of real data taken from an iron open-pit mine in Iran. The results of the case study indicated that the systematic uncertainty, inherent variability, and statistical uncertainty are, in order, the main sources of uncertainty on grade reconciliation process. Applying the correction factors to estimated grade values has increased the amount of grade reconciliation from 10%, at original condition, to 50%, at new condition, in the case study.